The Intricacies of Computational Medical Research: An Advanced Study Approach - Milan Toma; David Addepalli; Rosalyn Chan-Akeley (Recent Developments in Medicine and Medical Research Vol. 4, 2021)
Computational simulations of biological systems are an intrinsic element of engineering in medicine, allowing physicians the ability to visualize the pathophysiology behind a disease. Many biomedical applications require fluid–structure interaction analyses. Due to the inherent complexity of biological applications, which often include fluids and structures interacting together, the development of computational fluid–structure interaction models is necessary to achieve a quantitative understanding of their structure and function in both health and disease. Furthermore, the relationship between biological structures and the fluid that surrounds them is an integral part of their function. Hence, we contend that the use of fluid–structure interaction models in computational studies of biological systems is practical, if not necessary. The goal is to develop computational models to predict all human biological processes. These models are meant to guide us through the multitude of possible diseases affecting our organs and lead to more effective methods for disease diagnosis, risk stratification, medical management, and therapy. This chapter discusses the intricacies of computational medical research, namely concerning patient specificity and the validation of computational methods used.